Lobectomy with ipsilateral central lymph node dissection might be an appropriate surgical method for select cases of isthmic papillary thyroid carcinoma: a retrospective study with propensity scores matching analysis - Wang, Bin; Zhu, Chun-Rong; Wen, Hong; Fei, Yuan; Wu, Zhu-Juan; Liu, Hong; Yao, Xin-Min; Wu, Jian (Frontiers in Endocrinology, 2025)
ObjectiveThe study aimed to ascertain the appropriate surgical method for isthmic papillary thyroid carcinoma (PTC).MethodsWe reviewed the records of patients who underwent thyroid surgery for PTC in our institution from July 2018 to June 2024. The isthmus was categorized into central isthmus and paracentral isthmus. Data were compared to explore the risk factors of contralateral paratracheal lymph node metastasis (LNM) and the presence of more than 5 metastatic lymph nodes between patients with paracentral isthmic PTC and those with lobar PTC, and between patients with paracentral isthmic PTC and those with central isthmic PTC. Propensity score matching was used to identify a cohort of patients with similar baseline characteristics among patients with paracentral isthmic PTC and lobar PTC to minimize discrepancies in the number between the two groups.ResultsPrelaryngeal and/or pretracheal LNM was confirmed to be an independent risk factor for contralateral paratracheal LNM (OR = 3.43; 95%CI 1.74 – 8.92; p = 0.013) and presence of more than 5 metastatic lymph nodes (OR = 4.55; 95%CI 1.46 – 14.15; p = 0.009) in patients with paracentral isthmic PTC and lobar PTC. While, the location in the paracentral isthmus did not exhibit a significant association with them in these patients. Conversely, being located in the central isthmus was confirmed to be a risk factor for contralateral paratracheal LNM (OR = 4.67; 95%CI 1.53 – 14.21; p = 0.007) and the presence of more than5 metastatic lymph nodes (OR = 4.55; 95%CI 1.46 – 14.15; p = 0.009) among patients with isthmic (central and paracentral) PTC.ConclusionLobectomy with ipsilateral central lymph node dissection might be appropriate for paracentral isthmic PTC without prelaryngeal and pretracheal LNM. Total thyroidectomy with bilateral central lymph node dissection might be necessary for central isthmic PTC.